Frequency of Anemia of Chronic Disease in Patients with Behcet's Disease - Cicek, Demet; Kandi, Basak; Ilhan, Nevin; Dertlioglu, Selma Bakar; Demir, Betul (Turkish Soc Dermatology Venerology, 2007)
Background and Design: Anemia of chronic disorders is a mild to moderate anemia characterized by decreased serum iron, decreased total iron-binding capacity and increased iron stores. Anemia of chronic disorders occurs in a wide variety of diseases including cancer, chronic infections and inflammatory disorders.Behcet's disease is a chronic and inflammatory disease. There is a possibility of anemia of chronic disorders in Behcet's disease. But, frequency of anemia of chronic disorders in Behcet's disease was never evaluated in previous studies. Thus, we aimed to determine the frequency of anemia of chronic disease in Behcet's disease. Material and Method: The study included 40 patients with Behcet's disease and 20 healthy volunteers. Serum iron, hemoglobin, ferritin, UIBC and TIBC levels were assessed. Anemia was determined as hemoglobin levels <13.5 mg/dl for men and <12 mg/dl for women in patients and control group. It was interpreted; serum ferritin level <60 ng/ml were evaluated as iron deficiency anemia, and serum ferritin level >60 ng/ml were evaluated as anemia of chronic disease. Patients were divided into anemia of chronic disease and iron deficiency anemia subgroups. Results: Anemia of chronic disease and iron deficiency anemia frequencies were 10%, 17.5% in patients with Behcet's disease. All of patients who have anemia of chronic disease were in the group of active Behcet's disease. 15% of control group was determined iron deficiency anemia and anemia of chronic disease was not seen. There were no significant differences between age, sex, treatment disease duration and levels of serum iron, hemoglobin and ferritin of both groups (p>0.05). There was a significant correlation between leves of serum hemoglobin and ferritin (r=0.06 and p<0.001). Conclusions: In this study anemia of chronic disease and iron deficiency anemia frequencies were 10%, 17.5% respectively in patients with Behcet's disease.
Behçet hastalarinda kronik hastalik anemisi sikli?i
Keywords: Behcet's disease; anemia of chronic disease; iron deficiency anemia